STUDI TENTANG SANITASI LINGKUNGAN DI KELURAHAN NAN BALIMO KECAMATAN TANJUNG HARAPAN KOTA SOLOK - Tia Muliyanti Rismi; dedi Hermon (JURNAL BUANA, 2020)
This study aims to determine the characteristics of environmental sanitation in the Village of Nan Balimo, then to find out the system of disposal of liquid waste and solid waste in the Village of Nan Balimo and finally to find out community participation in maintaining environmental cleanliness in the Village of Nan Balimo District of Tanjung Harapan, Tanjung Harapan, Solok City. This type of research is descriptive with a quantitative approach. For data collection using a questionnaire / questionnaire, as well as for data processing using percentage analysis. The results of the research are: (1) The solid and liquid waste disposal system in Nan Balimo Village is classified as poor. This is evidenced from the data taken in the field that on average 50% of respondents still throw garbage in the river and the drainage of wastewater is still directed to the river, this has a very bad impact on the environmental ecosystem. (2) Community participation in environmental cleanliness is still very low, they assume that the cleansed environment will not change the appearance of their homes, the general mindset and the lack of socialization from the government are the factors causing the community's lack of awareness. (3) From the results of the description and analysis it can be concluded that the characteristics of environmental sanitation in the Village of Nan Balimo, Tanjung Harapan Subdistrict, Solok City is still low, this can be proven from the high percentage of people throwing sapah into the river, there is still no awareness in separating organic and non organic, the drainage of waste water is still flowed into the river and a sense of concern for environmental cleanliness is still low.